2020
DOI: 10.1017/ice.2020.397
|View full text |Cite
|
Sign up to set email alerts
|

Utility of repeat testing for COVID-19: Laboratory stewardship when the stakes are high

Abstract: As the Coronavirus disease 2019 continues to circulate, testing strategies are of the utmost importance. Given national shortages of testing supplies, personal protective equipment, and other hospital resources, diagnostic stewardship is necessary to aid in resource management. We report the low utility of serial testing in a low prevalence setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…A more recent study by Rearigh et al (11) conducted at an academic medical centre in Omaha, Nebraska also found similar results on a smaller cohort. Of the 275 patients tested, only 2 patients tested positive on serial testing after an initial negative result, for a yield of less than 1.0%.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A more recent study by Rearigh et al (11) conducted at an academic medical centre in Omaha, Nebraska also found similar results on a smaller cohort. Of the 275 patients tested, only 2 patients tested positive on serial testing after an initial negative result, for a yield of less than 1.0%.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, some clinicians recommend serial SARS-CoV-2 testing (testing at multiple points in time) for admitted patients with a high pre-test probability of infection (6). Some authors report that universal serial testing increases diagnostic yield considerably (10), while others have reported that universal serial testing is of very limited yield (11,12).…”
mentioning
confidence: 99%
“…Thus, repeat testing should be performed despite the fact that it increases the turnaround time and adds cost to the healthcare system. Diagnostic stewardship (correct time and method to collect samples) can be applied to decrease the number of inconclusive results, which in turn will conserve laboratory supplies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%